SOSIALISASI DALAM RANGKA MENINGKATKAN MINAT SISWA KELAS XII UNTUK MELANJUTKAN KE PERGURUAN TINGGI - Hidayatulloh, Alpiana; Pratama, Inda Arry; Zaidah, Alpi (JGEN : Jurnal Pengabdian Kepada Masyarakat, 2023)
The implementation of this activity was carried out at MA NWDI Kabar participants in this activity were class XII as many as 65 people consisting of Science and Social Sciences. This activity aims to carry out socialization in order to introduce tertiary institutions from the majors in tertiary institutions, organizations to the scholarships provided in tertiary institutions. The results of this activity were the number of students who enthusiastically participated and asked questions about the process that was passed to get the information conveyed. In addition, there were many students, around 50% of class XII students who..